Paper-fluorocarbon compound composite insulation dielectric spectrum test and analysis method

By reinforcing the fluorocarbon compound composite insulation samples by compounding the fluoric and NOMEX insulation paper-fluorocarbon compounds, and using broadband media spectrum testing technology to study its dielectric performance The problem realizes the development of stable dielectric and environmental protection materials in high -frequency environments.

CN119375562APending Publication Date: 2025-01-28XI AN JIAOTONG UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411610792.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In existing power transformers, the flammable and explosive properties of oil-paper insulating materials threaten safe and stable operation, and there is a lack of effective research on the dielectric properties of fluorocarbon compounds.

Method used

By compounding the fluoroconomotic compound insulation sample of fluoroconon-to-NOMEX insulation paper-fluorocarbon compound compound insulation samples, and using broadband media spectrum test technology to study its dielectric performance at different temperatures and frequencies.

Benefits of technology

The test and analysis of the response characteristics of the composite insulation material of the paper-fluorocarbon compounds, showing its excellent insulation performance and low loss characteristics, suitable for the needs of modern high-frequency power equipment, and provided new materials for environmental protection for environmental protection. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375562A_ABST
    Figure CN119375562A_ABST
Patent Text Reader

Abstract

The invention discloses a paper-fluorocarbon compound composite insulation dielectric spectrum test and analysis method, which comprises the following steps: carrying out surface cleaning and metal spraying treatment on a prepared paper-fluorocarbon compound composite insulation sample, and then formulating a test method for dielectric properties of the composite insulation sample at different frequencies and temperatures. And finally, testing the dielectric constant and the loss angle tangent of the sample by using a broadband dielectric spectrum tester to obtain the change relation of the dielectric constant and the loss angle tangent value of the composite insulation sample along with the frequency at different temperatures. The paper-fluorine composite insulating material has excellent insulating property and low-loss characteristic, and can keep stable dielectric property in a high-frequency environment, so that the requirements of modern high-frequency power equipment are met. The material adopts environment-friendly fluorine inert liquid, not only has good electrical and thermal properties, but also is environment-friendly, and meets the requirements of sustainable development. The invention provides a new material choice for improving the insulating property and the operation stability of equipment such as a power transformer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of engineering dielectrics and electrical engineering testing, and in particular to a test method for dielectric properties of a novel paper-fluorocarbon compound composite insulating material. Background Art

[0002] In power transformers, oil-paper insulation is widely used due to its excellent insulation performance and flexible heat dissipation characteristics. However, the flammability and explosion of transformer oil threatens the safe and stable operation of power transformers, which also poses new challenges to the design and performance of insulation materials for power transformers. Compared with traditional oil-paper insulation and solid insulation materials, the development of new environmentally friendly liquid and solid composite insulation materials is of great significance to the development of power transformers. Fluorocarbon liquids are used in electronics, electrical and medical cleaning fields due to their excellent physical and chemical properties, and their environmentally friendly characteristics such as transparency, low viscosity, non-toxicity, no flash point, non-combustion, and strong compatibility. In particular, the insulation, high thermal stability and chemical stability of fluorocarbon liquids make them show great application potential in the field of high-performance insulation.

[0003] Although fluorocarbon liquids have great potential in the field of insulation, there are relatively few studies on their dielectric properties. Existing studies have shown that the unique phase change cooling characteristics of fluorocarbon liquids can effectively improve the heat dissipation capacity of equipment, and are expected to play an important role in heat insulation and heat dissipation in power transformers. The present invention prepares paper-fluorocarbon composite insulation samples by compounding fluorocarbon liquids with Nomex insulation paper, and focuses on the dielectric property test method of fluorocarbon-paper composite insulation samples at different temperatures and frequencies. The broadband dielectric spectrum testing technology is used to study the dielectric constant and dielectric loss tangent of fluorocarbon-paper composite insulation samples at different frequencies. The polarization and dielectric relaxation characteristics of fluorocarbon-paper composite insulation samples are analyzed, which is of great significance to further promote the development, performance evaluation and environmental protection of power transformer insulation materials. Summary of the invention

[0004] The invention aims to realize the test of dielectric spectrum of paper-fluorocarbon composite insulation, and provide and analyze the dielectric response variation law of paper-fluorocarbon composite insulation at different frequencies and temperatures.

[0005] To achieve the above object, the method of the present invention comprises the following steps:

[0006] Step 1: Testing method for broadband dielectric spectrum data of paper-fluorocarbon composite insulation samples;

[0007] Step 2: Broadband dielectric spectrum data analysis of paper-fluorocarbon composite insulation samples;

[0008] The specific steps of testing the broadband dielectric spectrum of the paper-fluorocarbon composite insulation in step 1 are: using a dielectric spectrum tester to test the impregnated paper-fluorocarbon composite insulation sample, the sample thickness is 0.13mm, the size is 50mm×50mm sheet, and the gold spraying diameter range is 17-22mm; specifically including the following steps:

[0009] Step 1.1: The sample is first subjected to gold spraying treatment. Since it is a composite insulation structure of fluorocarbon liquid and solid paper, the sample is sprayed with an electrode with a diameter of 17 mm on the upper surface in contact with the electrode and a diameter of 22 mm on the lower surface in contact with the electrode. This ensures that the composite insulation structure sample can be in good contact with the electrode, thereby obtaining a dielectric spectrum under this thickness of composite insulation;

[0010] Step 1.2: First, the equipment needs to be preheated to ensure that the instrument reaches a stable state. At the same time, in order to prevent the equipment from being overheated and causing the fluorocarbons to volatilize and affect the test results, the preheating time is set to 30 minutes to ensure that the internal temperature and circuit of the equipment reach the best working state.

[0011] Step 1.3: Open the test software, set the experimental test frequency to 10-1~106Hz, repeat the sweep test 3 times, and set the maximum test voltage to 200V to avoid the influence of excessive voltage on the stability of the equipment test and the sample. Considering the volatility of fluorocarbon liquid at high temperature and the change of physical state at low temperature on the test results, the experimental test temperature is 20℃~80℃. Considering that the rapid heating rate will accelerate the volatilization rate of fluorocarbons, thus affecting the measurement of broadband dielectric spectrum of paper-fluorocarbon composite insulation at a certain temperature.

[0012] Step 1.4: Clamp the sample firmly on the test head, ensuring that the sample is in good contact with the test electrode without looseness or displacement. After correct installation, place the test head into the test cavity to maintain the stability of the sample during the test;

[0013] Step 1.5: Pay close attention to the real-time data of the experiment to ensure that the sample maintains a good working condition during the test, and adjust the experimental conditions in time according to the data changes, and use the liquid nitrogen temperature control system to adjust the experimental test temperature. Finally, save the data manually and ensure that the file format meets the requirements of subsequent analysis;

[0014] Step 1.6: Close the test software and turn off the power of the equipment in sequence according to the equipment's operating procedures. Before turning off the power, wait for the equipment to cool down completely, especially the test cavity and temperature control unit, and then remove the sample from the electrode and put it into the prepared sample bag.

[0015] The step 2 involves analyzing the broadband dielectric spectrum data of the paper-fluorocarbon composite insulation material obtained by the test, and specifically includes the following steps:

[0016] Step 2.1: Considering the broadband dielectric spectrum data of paper-fluorocarbon composite insulation at different temperatures and frequencies, the extended Debye model is used to analyze the experimental data and analyze the variation of dielectric properties with temperature and frequency;

[0017] Step 2.2: Combined with dielectric theory, analyze the variation law of broadband dielectric spectrum curve of paper-fluorocarbon composite insulation, and explain the dielectric properties by the variation mechanism of different polarization forms with applied frequency and temperature.

[0018] Beneficial effects of the present invention:

[0019] The present invention tests and analyzes the dielectric response characteristics of paper-fluorine composite insulation materials at different frequencies, and shows the following beneficial effects. Paper-fluorine composite insulation materials have excellent insulation properties and low loss characteristics, and can maintain stable dielectric properties in high-frequency environments, thereby meeting the needs of modern high-frequency power equipment. The material uses environmentally friendly fluorine inert liquid, which not only has good electrical and thermal properties, but is also environmentally friendly and meets the needs of sustainable development. The present invention provides a new material option for improving the insulation performance and operating stability of equipment such as power transformers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The figure is a flow chart for testing dielectric properties of paper-fluorocarbon composite insulation of the present invention;

[0021] Figure 2 This is a schematic diagram of the dielectric property testing method of the test paper-fluorocarbon composite insulation material of the present invention;

[0022] Figure 3 Broadband dielectric spectra of paper-fluorocarbon composite insulation materials at different temperatures. DETAILED DESCRIPTION

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] The technical solution and related principles of the present invention are described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0025] like Figure 1 and 2The figure shows a dielectric performance test process and principle diagram of a paper-fluorocarbon composite insulation sample provided by the present invention. In this embodiment, the method comprises the following steps:

[0026] Step S101: taking out the prepared paper-fluorocarbon composite insulation sample from the sealed bottle, and drying and removing dust from the surface;

[0027] Step S102: Spraying gold on the upper and lower surfaces of the treated sample respectively, spraying a circular electrode with a diameter of 17 mm on the upper surface in contact with the electrode, and spraying a circular electrode with a diameter of 22 mm on the lower surface in contact with the electrode. This gold plating size can better ensure that the composite insulating structure contacts the electrode to obtain accurate test results;

[0028] Step S103: clamp the gold-plated sample between the upper and lower test electrodes to ensure that the gold-plated electrode of the sample is in good contact with the test electrode without looseness or displacement;

[0029] Step S104: Open the test software on the computer; considering that the volatility of the fluorocarbon liquid at high temperature and the change of the physical state at low temperature will affect the test results, the test temperature is set to 20℃~80℃. Considering that a too fast heating rate will increase the volatility of the fluorocarbon and affect the accuracy of the test data, the temperature is measured at every 20℃ rise. The test is set to 10 -1 ~10 6 A frequency sweep test of Hz was performed to calibrate the data and the test was repeated 3 times. 20 frequency points were taken at equal logarithmic intervals every 10 times the frequency. In order to avoid the influence of excessive voltage on the stability of the test equipment and the paper-fluorocarbon composite insulation sample, the test voltage was set to a maximum of 200V and the sample thickness was set to 0.13mm.

[0030] Step S105: Click the test button in the software to obtain the broadband dielectric spectrum of the paper-fluorocarbon composite insulation at room temperature, i.e., the switch S 1 and S 2 Close. Compare with the expected test results. If there is a large difference, the sample thickness parameters can be fine-tuned until the material dielectric parameters at room temperature are consistent with the expectations, so as to ensure the correctness of the broadband dielectric spectrum data tested at different temperatures in the future.

[0031] Step S106: After the broadband dielectric spectrum data of the test material at room temperature is correct or corrected, the test head is placed in the temperature chamber. The test system changes the temperature in the chamber by regulating the liquid nitrogen temperature control system, and realizes online temperature monitoring through the electronic thermometer module to measure the broadband dielectric spectrum data of the paper-fluorocarbon composite insulation at different temperatures, and record and save the broadband dielectric spectrum data at different temperatures.

[0032] Step S107: Analyze the dielectric spectrum data obtained from the test, and explain the change pattern of the dielectric spectrum curve with temperature and frequency in combination with dielectric theory.

[0033] In the present invention, the broadband dielectric spectrum of the paper-fluorocarbon composite insulation is tested. The variation rules of the broadband dielectric spectra of the paper-fluorocarbon composite insulation and the oil-paper composite insulation at different temperatures and frequencies are consistent with the dielectric polarization theory, such as Figure 3 As shown. When an alternating electric field is applied to a dielectric, the charges inside the dielectric generate a response current driven by the electric field force. The essence of this is due to the polarization behavior and conductivity behavior of the charges. The polarization behavior inside the dielectric is classified according to the type of dielectric. The change in frequency will cause a significant change in the polarization intensity of some polarization behaviors, thereby obtaining a dielectric response spectrum within the test frequency range. For the study of the mathematical laws of the dielectric conductivity process and polarization process on frequency domain variables, the two most commonly used models are and The above formulas respectively represent the mathematical function expressions of the complex dielectric constant of the conductivity process and the complex dielectric constant of the polarization process, which is also called the Debye equation model. When there are displacement polarization, relaxation polarization and penetrating conductivity in the dielectric, the relative dielectric constant inside the dielectric under the action of the alternating electric field is as shown in the above formula. 0 is the DC conductivity; τ is the relaxation polarization time, and ε is the relative dielectric constant in vacuum, which is 8.85×10 -12 F / m. ε s is the relative dielectric constant of the medium under steady-state DC electric field, ε ∞ is the relative dielectric constant at optical frequency, independent of frequency and temperature.

[0034] The dielectric spectrum curve of paper-fluorocarbon composite insulation material is analyzed by combining dielectric theory. The dielectric response characteristics under different temperature and frequency conditions mainly include low-frequency conductivity characteristics, different relaxation polarization processes and dependence on temperature and frequency. Figure 3It can be seen that the relative dielectric constant and loss factor of the composite material in the low-frequency region change significantly, and it has obvious low-frequency conductivity characteristics; this is because the increase in temperature at low frequency promotes the thermal activation of the conductive ions inside the material, and the barrier required for the conductive ions to migrate in an electric field decreases, and more conductive ions participate in the charge transport process, which significantly increases the dielectric loss at low frequency. With the increase in frequency, the dielectric behavior in different frequency ranges is dominated by different polarization types. Among them, there is a more obvious interface polarization effect in the medium and low frequency regions, which is manifested as a gradual decrease in the relative dielectric constant with increasing frequency. From the perspective of the loss factor contributed by the interface polarization effect, it will increase first and then decrease with frequency. There is an obvious interface polarization effect inside the composite material. The interface between paper and fluorocarbon polymer becomes the main source of interface polarization. The difference in conductivity between different phases inside the material causes interface charge accumulation, and the increase in temperature further increases the carrier mobility and aggravates the interface polarization effect. In the high-frequency region, it can be seen that the dielectric loss tends to increase with increasing frequency, while the relative dielectric constant has been on a downward trend. In this frequency band, the loss factor shows a peak value that changes with frequency, and the relaxation polarization process is obvious in the high-frequency region. In this frequency band, the dynamic process of polar molecular groups reorienting under an external electric field can keep up with the changes in the external electric field. The consumed electric field energy increases, resulting in increased losses, and increased temperature has an enhancing effect on the number and activity of polar molecular segments. The relaxation frequency moves toward the high-frequency direction with increasing temperature, making it easier for polar groups to respond to electric fields at higher frequencies. At high frequencies, the relaxation polarization process mainly comes from insulating paper. When the temperature rises, the insulating paper is accompanied by the breakage and recombination of local molecular chains, resulting in an increase in the number of polar groups and a relaxation process that is more likely to occur.

[0035] The dielectric spectrum curve shows that the paper-fluorocarbon composite insulation material has obvious temperature and frequency dependence. Its relative dielectric constant shows a trend of increasing first and then decreasing with increasing temperature, and has been decreasing with increasing frequency. The loss factor shows a trend of decreasing first and then increasing with increasing temperature, and a trend of decreasing first, then increasing, and then decreasing with increasing frequency. This trend is related to the orientation polarization and thermal activation process of polar molecules. In the initial temperature rise stage, the increase in thermal energy leads to more active orientation polarization of polar molecules. The increase in the number of directional arrangements of polar molecules in the direction of the applied electric field leads to an increase in the dielectric constant. When the temperature rises to a certain extent, the drastic increase in the thermal motion of polar molecules interferes with the directional arrangement along the direction of the electric field, accompanied by the weakening of intermolecular interactions or the possibility that polar molecules reach saturated orientation, resulting in a decrease in the dielectric constant. The trend of the dielectric constant continuing to decrease with increasing frequency indicates that at higher frequencies, the fast polarization of electron displacement polarization and ion displacement polarization become dominant in the polarization process, while the slow polarization of polar molecules orientation polarization contributes less because it cannot follow the rapid change of the electric field. As for the change in loss factor, the initial decrease in loss factor is related to the optimization of the internal polarization process of the material. Within a certain temperature range, the orientation adjustment of polar molecules is more synchronized with the electric field, reducing the ineffective dissipation of energy. As the temperature further increases, internal friction and energy dissipation increase, causing the loss factor to rise again. In terms of the influence of frequency, the trend of the loss factor first decreasing, then increasing, and then decreasing may be related to the change in relaxation phenomena at different frequencies. In the medium frequency range, there may be one or more specific relaxation processes, and the loss factor will increase when the frequency matches the characteristic frequencies of these relaxation processes. Outside these specific frequencies, the loss factor shows a downward trend because the relaxation process fails to effectively respond to the rapid changes in the applied electric field.

[0036] The above description is only a preferred embodiment of the present invention and does not constitute any other form of limitation to the present invention. Any modification or equivalent change made based on the technical essence of the present invention still falls within the scope of protection required by the present invention.

Claims

1. A method for testing and analyzing dielectric spectra of paper-fluorocarbon composite insulation, characterized in that: The prepared paper-fluorocarbon composite insulation sample was surface cleaned and gold-sprayed, and then a test method for the dielectric properties of the composite insulation sample at different frequencies and temperatures was developed. Finally, a broadband dielectric spectrum tester was used to test the dielectric constant and loss tangent of the sample to obtain the relationship between the dielectric constant and loss tangent of the composite insulation sample at different temperatures and frequencies.

2. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: Surface cleaning treatment: Take the prepared paper-fluorocarbon composite insulation sample out of the sealed bottle and dry and remove dust from the surface.

3. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: The surface is gold-sprayed with a diameter range of 17-22mm. The upper and lower surfaces of the treated sample are respectively gold-sprayed. For this paper-fluorocarbon composite insulation structure, a circular electrode with a diameter of 17mm is sprayed on the upper surface in contact with the electrode, and a circular electrode with a diameter of 22mm is sprayed on the lower surface in contact with the electrode. This gold-plating size can better ensure the contact between the composite insulation structure and the electrode to obtain accurate test experimental results.

4. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: The electrodes in the dielectric properties test method clamp the gold-plated sample between the upper and lower test electrodes to ensure that the gold-plated electrode of the sample is in good contact with the test electrode without looseness or displacement.

5. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: The dielectric properties test method is cooled by liquid nitrogen. Considering the volatility of fluorocarbon liquid at high temperature and the change of physical state at low temperature, the test temperature is set to 20℃~80℃ and the test frequency is set to 10 -1 ~10 6 Hz, in order to avoid excessive voltage from damaging the stability of the equipment and the sample, the test voltage is set to a maximum of 200V and the sample thickness is set to 0.13mm.

6. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: Dielectric spectrum tester, select room temperature for 10 -1 ~10 6 Perform a Hz sweep test to calibrate the data and repeat this three times. If the data has high repeatability, the calibration is complete and subsequent measurements can be performed.

7. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: Dielectric spectrum test results and changes. After the sample is calibrated at room temperature, the test head is placed in the temperature chamber. The temperature and data are monitored in real time. After the temperature stabilizes, the dielectric constant and loss tangent value at different frequencies are measured.

8. The method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: According to the test results of dielectric spectrum, change the temperature, and repeat the above measurement steps after the temperature stabilizes in the next step. Record and save the data of the change of dielectric constant and dielectric loss tangent value of the sample at different temperatures with frequency.

9. A method for testing and analyzing dielectric spectrum of paper-fluorocarbon composite insulation according to claim 1, characterized in that: Dielectric spectrum test results and changes, and dielectric properties of test data analyzed based on HN dielectric theory.

10. A method of obtaining dielectric spectrum test data of a paper-fluorocarbon composite insulation sample using the test method in claims 1-9, and obtaining dielectric response performance.

Citation Information

Cited By

  • Food baking processing program control system and method

    CN120295102A